How Do Synchronous Lung Metastases Influence the Surgical Management of Children with Hepatoblastoma? An Update and Systematic Review of the Literature - Angelico, Roberta (Cancers (Basel), 2019)
Approximately 20% of children with hepatoblastoma (HB) have metastatic disease at diagnosis, most frequently in the lungs. In children with HB, lung metastatic disease is associated with poorer prognosis. Its treatment has been approached with a variety of methods that integrate chemotherapy and surgical resection. The timing and feasibility of complete extirpation of lung metastases, by chemotherapy and/or metastasectomy, is crucial for the surgical treatment of the primary liver tumor, which can vary from major hepatic resections to liver transplantation (LT). In children with unresectable HB, which can be surgically treated only by LT, the persistence of unresectable metastases after neoadjuvant chemotherapy excludes the possibility of recurring to LT with consequent negative impact on patients’ outcomes. Due to limited evidence and experience, there is no consensus amongst oncologists and surgeons across institutions regarding the surgical treatment for HB with synchronous metastatic lung disease. This narrative review aimed to update the current management of pulmonary metastasis in children with HB and to define its role in the decision-making strategy for the surgical approach to primary liver tumours.